First‐line pharmacotherapy for incident type 2 diabetes: Prescription patterns, adherence and associated costs. Issue 9 (29th June 2021) - Campbell, David J. T.; Campbell, Dennis B.; Ogundeji, Yewande; Au, Flora; Beall, Reed; Ronksley, Paul E.; Quinn, Amity E.; Manns, Braden J.; Hemmelgarn, Brenda R.; Tonelli, Marcello; Spackman, Eldon
Abstract: Aims: To use real‐world prescription data from Alberta, Canada to: (a) describe the prescribing patterns for initial pharmacotherapy for those with newly diagnosed uncomplicated type 2 diabetes; (b) describe medication‐taking behaviours (adherence and persistence) in the first year after initiating pharmacotherapy; and (c) explore healthcare system costs associated with prescribing patterns. Methods: We employed a retrospective cohort design using linked administrative datasets from 2012 to 2017 to define a cohort of those with uncomplicated incident diabetes. We summarized the initial prescription patterns, adherence and costs (healthcare and pharmaceutical) over the first year after initiation of pharmacotherapy. Using multivariable regression, we determined the association of these outcomes with various sociodemographic characteristics. Results: The majority of individuals for whom metformin was indicated as first‐line therapy received a prescription for metformin monotherapy (89%). Older individuals, those with higher baseline A1C and those with no comorbidities, were most likely to be started on non‐metformin agents. Adherence with the initially prescribed regimen was suboptimal overall, with nearly half (48%) being non‐adherent over the first year. One‐third of those who started metformin discontinued it in the first 3 months. Those started on non‐metformin agents had roughly twice the healthcare costs, and five to seven times higher medication costs, compared to those started on metformin, in the first year after starting therapy. Conclusions: With the addition of new classes of medications, healthcare providers who look after those with type 2 diabetes have more pharmaceutical options than ever. Most individuals continue to be prescribed metformin monotherapy. However, adherence is suboptimal, and drops off considerably within the first 3 months.